A NEW SPECIES OF CYPRINID FISH: Puntius bunau FROM THE SETURAN BASIN OF INDONESIAN BORNEO - Ike Rachmatika (Treubia, 2004)
Puntius bunau, neto species from the Seturan Watershed, Bulungan, East Kalimantan, Indonesia is distinguished from its congellers by the combination of the following characters: a black triangular bar all the side of the body under the dorsal fill, black spots behind the opercle, a black bar all the edge of the anal fill, 22-23 lateral line scales, predorsal profile convex, and eye diameter 21.28-29.73% of head length.